Study the Effect of Residence Time Parameters on Thermal Cracking Extract Phase Lubricating Oil - Obyed, Saleem Mohammed (Al-Khwarizmi Engineering Journal, 2019)
This work studies with produce of light fuel fractions of gasoline, kerosene and gas oil from treatment of residual matter that will be obtained from the solvent extraction process as by product from refined lubricate to improve oil viscosity index in any petroleum refinery. The percentage of this byproduct is approximately 10% according to all feed (crude oil) in the petroleum refinery process. The objective of this research is to study the effect of the residence time parameter on the thermal cracking process of the byproduct feed at a constant temperature, (400 °C). The first step of this treatment is the thermal cracking of this byproduct material by a constructed batch reactor occupied with control device at a selective range of residence time (duration of the reaction) 30, 45, 60 and 75 minutes respectively at a constant temperature (400 °C). The conversion of this byproduct by thermal cracking process reaches 90% for all these residence times. The second step for this study is distillation this cracked extract liquid by atmospheric distillation device, for these various residence times according to the ASTM-D86 method, to obtain light fuel fractions of gasoline, kerosene and gas oil,in volume percentages 15, 75 and 0 for residence time 30, 5, 60 and 25, for residence time 45, 5, 10, 75, for residence time 60 and (10, 60 and 20) for residence time 75, which separates according to its boiling point. The major physical and chemical properties for feed (extract phase) and cracking extract liquid with its light fuel fractions were experimentally calculated and the results refer to acceptable properties compared with other standard property.